Measuring tactile sensitivity and mixed-reality-assisted exercise for carpal tunnel syndrome by ultrasound mid-air haptics - Akdağ, Mehmet Akif; Menekşeoğlu, Ahmet Kıvanç; Seğmen, Hatice; Gözek, Berk; Korkmaz, Merve Damla; Güçlü, Burak (Frontiers in Neuroscience, 2024)
Introduction: Carpal tunnel syndrome (CTS) is the most common nerve entrapment neuropathy, which causes numbness and pain in the thumb, the index and middle fingers and the radial side of the ring finger. Regular hand exercises may improve the symptoms and prevent carpal tunnel surgery. This study applied a novel ultrasonic stimulation method to test tactile sensitivity in CTS and also a mixed-reality-assisted (MR-assisted) exercise program which measured hand movements and provided haptic feedback for rehabilitation. Methods: Twenty patients with mild unilateral CTS took part in the experiments. A mid-air haptics device (Ultrahaptics STRATOS Explore) was used to apply amplitude-modulated ultrasound waves (carrier frequency: 40 kHz) onto the skin to create tactile stimulation mechanically. Participants performed a two-alternative forced-choice task for measuring tactile thresholds at 250-Hz modulation frequency. They were tested at the index fingers and the thenar eminences of both hands. Additionally, fifteen CTS patients used an MRassisted program to do hand exercises with haptic feedback. Exercise performance was assessed by calculating errors between target and actual hand configurations. System Usability Scale (SUS) was adopted to verify the practical usability of the program. Results: Thresholds at the thenar eminences of the affected and healthy hands were not significantly different. While the thresholds at the healthy index fingers could be measured, those of the affected fingers were all higher than the stimulation level produced by the maximum output from the ultrasound device. In the exercise program, a significant positive correlation (ρ = 0.89, p < 0.001) was found between the performance scores and the SUS scores, which were above the criterion value established in the literature. Discussion: The results show that thenar tactile sensitivity is not affected in mild CTS as expected from the palmar cutaneous branch of the median nerve (PCBm), but index finger threshold is likely to be higher. Overall, this study suggests that mid-air haptics, with certain improvements, may be used as a preliminary test in the clinical setting. Moreover, the device is promising to develop gamified rehabilitation programs and for the treatment follow-up of CTS.